Case Report: Anencephaly On G2p1a0 Gravida 16-17 Weeks Pregnant Women With Covid 19 Mild Symptoms - Sutrisno, Jenri; Darmi, Geitha Puspita; Tambunan, David Oktavianus (Jurnal Health Sains, 2023)
Background: Anencephaly is severe congenital malformation of the central nervous system (CNS), with complete or partial absence of the cranium and brain. The incidence of this case is estimated to be between 1-5 events per 1000 births. Anencephaly arises from an embryonal defect before day 28 so that there is no closure of the anterior neuropore (cranial end of the neural tube). Case Summary: Case report about patient woman aged 21 years with COVID-19 infection who never had an ultrasound in the first trimester with complaints of abdominal pain a day ago, diminished fetal movement, there was not a release of blood show and mucus. An ultrasound examination performed in the second trimester and vaginal delivery is performed. Conclusion: Anencephaly is a malformation that has a high mortality according to the failure of the closure of the sefic part of the neural tube. The ISUOG guidelines recommend that ultrasonography be performed on pregnant women between 11 and 13 weeks. Through this paper, an explanation of the transabdominal and transvaginal 2D grayscale ultrasound examination to assess crown rump length and cranium at 11-13 weeks of pregnancy can detect anencephaly early.